Morning Sermon Culture as a Strategy to Strengthen Character Education at SDN 13 Penarik - Siti Kholifah; Nanda Dwi Pamungkas; Nur Hidayat; Aziza Aryati (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study aims to describe the morning cultum culture as a strategy for strengthening students' character education at SDN 13 Penarik. The focus of this study is the implementation of the morning cultum program in building students' character and the driving and inhibiting factors in its implementation. The research method used is a descriptive method with a qualitative approach. Data were collected through interviews, observation, and documentation. Data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions, with source triangulation as a data validity technique. The results of the study indicate that the implementation of the morning cultum is carried out through three stages, namely planning, implementation, and evaluation. The cultum activity has a positive impact on the formation of students' character, such as fostering religious values, discipline, responsibility, politeness, and self-confidence. The driving factors for the implementation of the cultum include school support, student enthusiasm, relevant materials, and adequate facilities and infrastructure. Meanwhile, the inhibiting factors include the lack of focus of some students, low self-confidence, limited time, and differences in student character. Based on the results of the study, the morning cultum culture is effective as a strategy for strengthening students' character education at SDN 13 Penarik.